2020
DOI: 10.1097/sga.0000000000000497
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gum Chewing on Abdominal Pain and Nausea Caused by Polyethylene Glycol Solution Used for Intestinal Cleansing Before Colonoscopy

Abstract: Gum chewing is known to have a positive effect on intestinal motility. Most studies have examined its effect on ileus, but there has been no discussion of the effects of polyethylene glycol used in preparation for colonoscopy. The purpose of this study was to determine the effect of gum chewing on abdominal pain and nausea caused by polyethylene glycol solution used for intestinal cleansing before colonoscopy. The study was planned as a single-center, randomized, controlled experimental study. The research sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Similar to this finding, Woo et al also revealed that the main adverse events of PEG/Asc for intestinal preparation were nausea and abdominal distention (22). Several reports have demonstrated that gum chewing had a positive effect on abdominal pain and nausea caused by PEG-ELS, and it may be recommended for patients (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this finding, Woo et al also revealed that the main adverse events of PEG/Asc for intestinal preparation were nausea and abdominal distention (22). Several reports have demonstrated that gum chewing had a positive effect on abdominal pain and nausea caused by PEG-ELS, and it may be recommended for patients (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%